Salivary interleukin-1 levels in oral squamous cell carcinoma: A case-control study - Dushyantsinh Vala; Jill Shah; Arman K Purba; Tarang Mehta; Anuj V Mansata; Sultan A Almalki; Ramanpal S Makkad (Journal of Pharmacy and Bioallied Sciences, 2024)
Objective: Oral squamous cell carcinoma (OSCC) is a prevalent malignancy with a significant impact on global health. The identification of non-invasive biomarkers for early detection and monitoring of OSCC remains crucial. Methods: A total of 100 subjects, comprising 50 patients with histopathologically confirmed OSCC and 50 age- and sex-matched healthy controls, were enrolled in the study. Salivary samples were collected from all participants and analyzed using enzyme-linked immunosorbent assays (ELISA) to measure IL-1 levels. Clinical data, including demographic information, smoking habits, and alcohol consumption, were obtained from patient records. Results: The mean salivary IL-1 level was significantly higher in OSCC patients compared to healthy controls (P < 0.001). Furthermore, subgroup analysis demonstrated that advanced stages of OSCC correlated with significantly elevated IL-1 levels when compared to early-stage OSCC (P < 0.05). Additionally, high salivary IL-1 levels were associated with a more aggressive tumor phenotype and poorer prognosis, as reflected by tumor size, lymph node metastasis, and overall survival (P < 0.01). Conclusion: This case-control study provides compelling evidence that salivary Interleukin-1 (IL-1) levels are significantly elevated in patients with OSCC.